Is incorporation (with Iimited Iiability) too easily available ? - Ziegel, Jacob (Les Cahiers de droit, 1990)
The incorporation of new businesses in Canada is remarkably cheap and easy, both under the Canada Business Corporations Act and under the provincial corporations statutes. The benefits conferred on shareholders by incorporation are obvious and well known, particularly the advantage of limited liability. Easy incorporation however also imposes significant burdens on the corporation's voluntary and involuntary creditors if the corporation cannot meet its liabilities. The author examines the various statutory and judicially created techniques for restraining the abuse of the corporate form, and finds them seriously deficient. Nevertheless, he sees no likelihood of the legislature reversing a century old trend either by making incorporation much more difficult or by denying directors or shareholders in closely held corporations the protection of limited liability. He concludes therefore that ''second order'' remedies are much more realistic, even if less efficient. He also recommends several new remedies, including the requirement that all corporations must file a copy of their financial statements in a public office and that directors will be held personally responsible for the corporation's debts if the corporation continues to trade when it is clear that it is insolvent and likely to remain so.